Phenomenon of Diaspora in The Preservation of National Culture on Example of Russian Diaspora in Bolivia - Elena Serukhina (Jurnal Ilmiah Hubungan Internasional, 2018)
Globalization covers the most diverse spheres of human life, including social, where the processes of migration and globalization of culture take on special significance. Cultures arise and develop, interacting with each other. And the first field of this interaction is the diaspora. Diaspora is the environment where culture is directly developed and enriched. The development of diasporas is carried out by spreading the culture, values and traditions of their people, but at the same time integrating into society with a different culture, which implies the acquisition of new socially and spiritually significant qualities. The psychological reason for the emergence of the diaspora is that people far from their homeland begin to understand, appreciate and even more love their native culture. The development of the modern world is characterized, as we know, by globalization. Can the phenomenon of the diaspora in modern social life be associated with it? No, because the diaspora is directly connected with culture, while globalization is opposed to culture. Globalization is aimed at unification, ignoring the problem of cultural identity. Globalization involves the erasure of cultural features, the loss of cultural, ethnic, religious differences. But at the same time, globalization contributes to the growth of population migration, which leads to an increase in the number of diasporas abroad. The rapid growth of immigrant communities and their institutionalization forced to talk about "the diasporaization of the world" as one of the scenarios for the development of mankind. One way or another, this process deepens and takes more and more new forms, and the role of diasporas and their influence are intensified.